الأسلوب الأنيق للحوارات القرآنية في توضيح الفتن الواردة في قصص سورة الكهفThe Elegant Approach of the Qur’ānic dialogues in clarifying the Temptations mentioned in the Stories of Surat Al-Kahf (Al-Qamar, 2020)
This article investigates and annotates the four stories of Surat Al-Kahf that are related to one axis. It brings together the four temptations in human life, which are: the trial of religion (in the story of the people of the cave), the trial of money (in the story of the owner of the two gardens), the trial of knowledge (in the story of Moses and Khidr) and the trial of power (in the story of Dhu al-Qarnayn). These temptations are severe on people, and the main driver of them is Satan, who embellishes these temptations- As for the stories of Surat Al-Kahf, each one talks about one of these severe temptations, and then comes a comment on the infallibility of these temptations.
Keywords: Surat Al-Kahf; Temptations; Dhu al-Qarnayn; Infallibility